Insulin-Dependent Diabetes Mellitus and the Pregnancy Outcomes: A Retrospective Study in the Pediatrics Department of Tripoli University Hospital – Tripoli, Libya (Razi Medical Journal, 2025)
This retrospective study aimed to investigate the association between Insulin-Dependent Diabetes Mellitus (IDM) and adverse maternal, fetal, and neonatal outcomes, with a focus on glycemic control, treatment modalities, and predictors of complications. Medical records of 35 singleton pregnancies with IDM (type 1 [T1DM], type 2 [T2DM], or gestational diabetes [GDM]) managed at a tertiary care center between January and December 2024 were analyzed. Data included maternal demographics, glycemic metrics (fasting/postprandial glucose, HbA1c), treatment regimens (diet, oral hypoglycemic agents [OHA], insulin), pregnancy complications, and neonatal outcomes. Statistical analyses employed descriptive statistics, chi-square/t-tests, and multivariate logistic regression. The results showed that the mean maternal age was 36 years (SD ±5.82), with 60% (n=21) aged >35 years. Diabetes subtypes included GDM (52.9%), T2DM (35.3%), and T1DM (11.8%). Poor glycemic control (38.2%) correlated with a tenfold increased macrosomia risk (OR=10, p=0.028). Maternal complications included infections (62.9%), pre-eclampsia (37.1%), and preterm labor (28.6%). Neonatal outcomes revealed cesarean delivery in 74.3%, hypoglycemia (62.9%), and respiratory distress syndrome (65.7%). Pre-gestational diabetes (T1DM/T2DM) was associated with higher respiratory distress rates (p=0.048) compared to GDM. Mixed insulin-OHA therapy increased fetal distress risk (100%, p=0.046). IDM significantly elevates risks of maternal-fetal complications, particularly with poor glycemic control and advanced maternal age. Findings underscore the need for stringent glucose monitoring, preconception counseling, and tailored antenatal care. Policy reforms should prioritize multidisciplinary management and equitable access to continuous glucose monitoring (CGM) in high-risk populations
Keywords: Insulin-Dependent Diabetes, Gestational Diabetes, Pregnancy Outcomes, Macrosomia